Integrated Analysis of Face Similarities in Twins - Blessy, Y. Angel (International Journal of Computer Sciences and Engineering, 2025)
Comparison identical twins using their face images are a challenge in biometrics. This paper presents experiments done in facial recognition using data from a set of images of twins. Identical twins have the closest genetics-based relationship and therefore, the maximum similarity between face is expected to be found among identical twins. Facial comparision techniques should be able to operate even when similar-looking individuals are encountered of identical twins. The capability of biometric techniques to distinguish between the twins features of multiple reasons. Human face matching capability is often considered as a benchmark for assessing and improving automatic face recognition techniques. This study gives us some clues and shows the various aspects of personality are differently subjected.